The study of relationship between cancer markers and age of patient in primary and metastatic paraffinized breast cancer tissue / Nur Azimah Osman - Osman, Nur Azimah (2009)
Breast cancer is a major problem among females all over the world. It is the most common cancer among Malaysian women with a prevalence of 39.5 per 100 000 population and consisting of 31% of all female cancers in 2003. There were many factors contributed to this disease including social demography, environmental and genetic. Tumor marker is a substance produces by tumor cells in order to distinguish tumor and normal cells. A total of 26 section paraffinized breast cancer tissues were used to study the relationship between cancer markers and social demography. All the paraffinized breast cancer tissues were reclassified according to the histologic grade (Nottingham Grading System) into grade I (9 samples), grade II (9 samples), grade III (6 samples) and there were 2 samples with unknown grade. Statistical analysis using chi square analysis shows that there was significant difference between Nottingham grading system with hematoxylin and eosin staining (< 0.05). H&E staining is not suitable to be applied as a method for breast cancer grading. Four breast cancer markers namely estrogen receptor (ER), progesterone receptor (PR), c-erbB-2 and hMAM were related with the age of breast cancer patients. The mean age of the patient s was 53.3 (SD=10, median 52). Genomic DNA extractions from the samples were achieved by using DNeasy Blood and Tissue Kit (Qiagen, Germany). The detection of hMAM DNA amplification was investigated by using Polymerase Chain Reaction (PCR). Breast cancer cell line (MCF-7), serum and plasma were used as positive controls whilst serum and plasma from normal patients were used as negative controls for the amplification of hMAM DNA. The relationship between cancer markers and age of patient in primary and metastatic paraffinized breast cancer tissue were studied by categorical and relationship modeling (C&R). The variation of relationship between them could provide a better prognostic for the management of breast cancer patients.